The imperatives of social media entrepreneurship for employment generation and cybercrime reduction among youths in Nigeria - Odoyi, Carol Dixon; Olatunji, Rotimi Williams (Institute for Advanced Science Social, and Sustainable Future, 2025)
Background: Social media have potentials for entrepreneurship, yet many young people misappropriate and abuse them to perpetrate cybercrime and other anti-social acts. Accordingly, this paper presents the outcome of an empirical research on the imperatives of social media entrepreneurship for employment generation and cybercrime reduction among youths in Nigeria. Methods: The objectives of the study were to examine the level of awareness of social media channels for entrepreneurship, the types of social media channels accessed for entrepreneurship, as well as the gratifications derived from social media channels among youths. The study was anchored on uses and gratifications theory. It adopted the descriptive survey research design, utilising the multi-stage sampling technique to select a sample size of 384 youths aged between 18 and 29 years. A questionnaire instrument designed by the researchers for data collection was deployed, while data were analysed using mean and standard deviation. Findings: On a 4-point Likert scale, the findings of the study revealed that some youths in Rivers State are barely aware of the potentials of social media for entrepreneurship. Among 384 respondents aged 18–29, 51% were aged 18–19; 78.9% agreed that social media increases sales and knowledge, 74.7% accessed Blogs, Facebook, Instagram, and WhatsApp for entrepreneurship, and a grand mean of 2.97 confirmed that social media use significantly improved youths’ livelihoods, market understanding, and wealth creation in Rivers State, Nigeria. Conclusion: Based on the findings, the researcher concluded that harnessing social media for entrepreneurship impacts positively on employment generation, poverty reduction, and leads to cybercrime reduction among youths, thus strengthening the attainment of the United Nations’ Sustainable Development Goal 1, amongst others. Novelty/Originality of this article: This article presents the outcome of an empirical research on the imperatives of social media entrepreneurship for employment generation and cybercrime reduction among youths in Nigeria.